Continental impacts of water development on waterbirds, contrasting two Australian river basins: Global implications for sustainable water use - Kingsford, Richard T.; Bino, Gilad; Porter, John L. (Global change biology, 2017)
The world's freshwater biotas are declining in diversity, range and abundance, more than in other realms, with human appropriation of water. Despite considerable data on the distribution of dams and their hydrological effects on river systems, there are few expansive and long analyses of impacts on freshwater biota. We investigated trends in waterbird communities over 32 years, (1983–2014), at three spatial scales in two similarly sized large river basins, with contrasting levels of water resource development, representing almost a third (29%) of Australia: the Murray–Darling Basin and the Lake Eyre Basin. The Murray–Darling Basin is Australia's most developed river basin (240 dams storing 29,893 GL) while the Lake Eyre Basin is one of the less developed basins (1 dam storing 14 GL). We compared the long‐term responses of waterbird communities in the two river basins at river basin, catchment and major wetland scales. Waterbird abundances were strongly related to river flows and rainfall. For the developed Murray–Darling Basin, we identified significant long‐term declines in total abundances, functional response groups (e.g., piscivores) and individual species of waterbird (n = 50), associated with reductions in cumulative annual flow. These trends indicated ecosystem level changes. Contrastingly, we found no evidence of waterbird declines in the undeveloped Lake Eyre Basin. We also modelled the effects of the Australian Government buying up water rights and returning these to the riverine environment, at a substantial cost (>3.1 AUD billion) which were projected to partly (18% improvement) restore waterbird abundances, but projected climate change effects could reduce these benefits considerably to only a 1% or 4% improvement, with respective annual recovery of environmental flows of 2,800 GL or 3,200 GL. Our unique large temporal and spatial scale analyses demonstrated severe long‐term ecological impact of water resource development on prominent freshwater animals, with implications for global management of water resources. Long‐term declining trends in waterbird numbers, at the total numbers, different species and functional response groups, were detected in the Murray–Darling Basin, with its rivers developed by dams. In comparison, there were few trends in the similarly sized but undeveloped Lake Eyre Basin. These two river basins cover near one‐third of the Australian continent. These trends in waterbird numbers were consistent at the scale of the entire basin, the two main rivers in each basin and for ten of the most important wetlands in each river basin. These results were from surveys over more than three decades and indicate the long‐term impacts of water resource developments on ecosystems, critical for rehabilitation and development of rivers around the world.